2014
DOI: 10.1016/j.aju.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

3-year results of transvaginal cystocele repair with transobturator four-arm mesh: A prospective study of 105 patients

Abstract: ObjectivesTo evaluate the long-term efficacy and safety of transobturator four-arm mesh for treating cystoceles.Patients and methodsIn this prospective study, 105 patients had a cystocele corrected between January 2004 and December 2008. All patients had a symptomatic cystocele of stage ⩾2 according to the Baden–Walker halfway stratification. We used only the transobturator four-arm mesh kit (Surgimesh®, Aspide Medical, France). All surgical procedures were carried out by the same experienced surgeon. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…This is very high considering the complications some of the patients reported. Good subjective results are also found in the published studies [19], Kdous reported an overall satisfaction score in VAS of 71,4% [21]. Concerning the urinary features, all of the items evaluated improved in our study.…”
Section: Commentsupporting
confidence: 87%
See 3 more Smart Citations
“…This is very high considering the complications some of the patients reported. Good subjective results are also found in the published studies [19], Kdous reported an overall satisfaction score in VAS of 71,4% [21]. Concerning the urinary features, all of the items evaluated improved in our study.…”
Section: Commentsupporting
confidence: 87%
“…Early complications reported in the literature include visceral injuries (bladder, rectum), bleeding, hematoma, acute urine retention, fever, mesh infection, thrombophlebitis and urinary tract infection [10,21,24]. In this study, the small rectal perforation could be repaired intraoperatively and the mesh was placed, with no further complications.…”
Section: Commentmentioning
confidence: 84%
See 2 more Smart Citations
“…Mean ambulation were similar in both groups and mean hospital stay was insignificantly different between both groups the latter being relatively long as compared to most studies due to associated surgeries done in some patients, however, it was more or less similar to the mean hospital stay in the study done by [11].…”
Section: Discussionmentioning
confidence: 69%